FLORISTIC DIVERSITY AND COMPOSITION ALONG AN ALTITUDINAL GRADIENT IN CHANCHAMAYO, FORESTS OF CENTRAL PERU - GIACOMOTTI, José (2021)
The montane and premontane forests extend along the Andes mountains, presenting different ecosystems and a great diversity of species of wild flora and fauna. The objective of this research was to evaluate the tree diversity and the floristic composition in six permanent plots of one hectare, located in the montane and premontane strata along an altitudinal gradient between 800 and 3000 masl, in the province of Chanchamayo, in forests of Central Peru. In the field phase, all trees with a DBH (diameter at breast height) greater than or equal to 10 cm were evaluated. Values of 425 to 696 individuals per hectare, and of 45 to 146 species per hectare were recorded in the six plots. The results of the floristic composition in the plots located in the montane forests (1500 to 3000 masl), indicated that the most important families overall in terms of abundance of individuals and number of species were Lauraceae, Melastomataceae, Cunoniaceae and Rubiaceae. While, in the permanent plots of the premontane forests (800 to 1500 masl), the most important families were Moraceae, Fabaceae and Lauraceae. The results obtained show that the diversity and floristic composition change according to the altitudinal stratum to which they belong, changing the floristic composition of forests according to the altitudinal range where they are located.